MELATONIN IMPLANT INDUCES ESTRUS AND ALLEVIATES OXIDATIVE STRESS IN SUMMER ANESTRUS BUFFALO - SINGH, B; GHUMAN, SPS; CHEEMA, RS; BANSAL, AK (The Indian Journal of Animal Reproduction, 2016)
Summer anestrus buffalo were divided into control (n=29) and treatment group (n=41). Treated buffalo were subcutaneously inserted melatonin implants @18mg/50kg body wt. Estrus signs were observed till 35 days post-treatment and estrus induction rate (%) was recorded. Blood samples were collected at weekly intervals, 7 days prior to insertion of implant until day 35 after insertion of implant. Estrus induction rate was higher (χ2=3.19, p<0.05) in melatonin-implanted buffalo (65.8%) as compared to control (41.4%). Lipid peroxide (LPO) concentrations reduced (p<0.05) in melatonin-implanted buffalo from day 28 onwards as compared to values in pre- reatment period and controls. Antioxidant enzymes (Glutathione Peroxidase, Glutathione Reductase, Superoxide dismutase and Catalase) showed an increasing trend following melatonin-treatment and remained elevated until day 35 (p<0.05); however, no such phenomenon was recorded in control buffalo. In conclusion, the present study demonstrated the effectiveness of melatonin for inducing estrus and alleviation of oxidative stress in summer anestrus buffalo.